(untitled) (Malay Literature, 2018)
Dain Said is one of the most reputable Malaysian film directors. Two of his films, Bunohan (2011) and Interchange (2016), not only won him awards for best film and best director but were also screened in many respected world film festivals. Bunohan and Interchange have a reputation of being different from many ordinary contemporary Malay films. Both films contain the similar theme of killing in their plots with a dark noirist approach, but killing is only on the surface of their multi-layered narratives. In both films, Dain is interested in the interweaving myth, imperialism and capitalism in the conflict of tradition and modernisation. Even though myth has been imbued with fantastic elements, it becomes part of the ideological process of naturalisation and has its own role in the origin of the race, history, and identity of a country. Colonialisation and capitalism have been gradually destroying traditional cultures and myths that are part of a nation’s ideology. This essay analyses how traditional cultures and mythologies should become the important elements in resisting the dangers of neo-colonialism that is called globalisation. Here, the films Bunohan and Interchange have proved that Dain Said is a film auteur in his own class. Keywords: myth, colonialism, auteur, Malay film, neo-noir